2017
DOI: 10.24200/sci.2017.4105
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible one-pot synthesis of pyrazolopyridines catalyzed by Fe3O4@SiO2-SO3H nanocatalyst under microwave irradiation

Abstract: Abstract. Fe3O4@SiO2-SO3H nanocatalyst has been used as an e cient catalyst for the preparation of pyrazolopyridines by a multi-component reaction of ethyl acetoacetate, aldehyde, hydrazine hydrate, and ammonium acetate under microwave irradiation. Atom economy, wide range of products, excellent yields in short times, use of microwave as green method, reusability of the catalyst, and little catalyst loading are some of the important features of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Elemental analysis results showed that the content of nickel, aluminum, and oxygen in the NiAl 2 O 4 spinel nanocrystals was 48.56, 15.13, 36.31 (wt%), respectively. As a result of our great interest in preparation of heterocyclic compounds by applying heterogeneous catalysts, [26,27] herein we wish to report an efficient procedure to synthesize 2,3-dihydroquinazolin-4(1H)-one derivatives through a threecomponent one-pot condensation of isatoic anhydride, aromatic aldehyde, and primary amines/ or ammonium acetate using NiAl 2 O 4 spinel nanocrystals as catalysts under microwave irradiation (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analysis results showed that the content of nickel, aluminum, and oxygen in the NiAl 2 O 4 spinel nanocrystals was 48.56, 15.13, 36.31 (wt%), respectively. As a result of our great interest in preparation of heterocyclic compounds by applying heterogeneous catalysts, [26,27] herein we wish to report an efficient procedure to synthesize 2,3-dihydroquinazolin-4(1H)-one derivatives through a threecomponent one-pot condensation of isatoic anhydride, aromatic aldehyde, and primary amines/ or ammonium acetate using NiAl 2 O 4 spinel nanocrystals as catalysts under microwave irradiation (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] Surveying in the literatures shows that a number of protocols have been reported for the preparation of tetrahydrodipyrazolopyridine derivatives. [30][31][32][33][34][35][36] Due to some drawbacks including use of unsafe reagents and solvents, non-recyclable and toxic catalysts, harsh workup protocol, and long reaction time with low practical yield, all of these methods are restricted. As a result, despite of the remarkable improvements, easy and mild methods in the presence of recoverable catalyst are highly demanded for the synthesis of tetrahydrodipyrazolopyridines.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Polshettiwar et al reported fibrous nanosilica (KCC-1), with the high surface area (typically >700 m 2 /g), broad pore size distribution, large pore sizes, [25,26] ease of surface modification, low density, stability and low toxicity with good biocompatibility. [9,11,12] This Dendritic fibrous nanosilica showed special activities in vast fields such as heterogeneous catalysis, [27] gas capture, solar energy harvesting, energy storage, [28] medical diagnosis, targeting of drugs, [7,[29][30][31] DNA adsorption [26] drug delivery applications, [32] bio sensing [33] and CO 2 Mitigation. [34] In this study, we reported the use of Fe 3 O 4 @KCC-1-nPr-NH 2 as an advanced novel nanocatalystis for the synthesis of tetrahydrodipyrazolopyridine (5a-m) compounds by multicomponent reaction of aromatic aldehydes, hydrazinehydrate (or phenylhydrazinehydrate), ethyl acetoacetate (or diethylmalonate) and ammonium acetate under reflux conditions in ethanol as a solvent (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, surface functionalized mesoporous systems have appeared as one of the most significant research areas in the concerning of advanced functional materials. Particularly, Polshettiwar et al reported fibrous nano‐silica (KCC‐1), with the high surface area (typically >700 m 2 /g), broad pore size distribution, large pore sizes, ease of surface modification, low density, stability and low toxicity with good biocompatibility . This Dendritic fibrous nanosilica showed special activities in vast fields such as heterogeneous catalysis, gas capture, solar energy harvesting, energy storage, medical diagnosis, targeting of drugs, DNA adsorption drug delivery applications, bio sensing and CO 2 Mitigation …”
Section: Introductionmentioning
confidence: 99%